2017
DOI: 10.2989/16085906.2017.1380677
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of the barriers to antiretroviral therapy initiation among children 2 to 18 months of age in Swaziland

Abstract: HIV/AIDS remains one of the leading causes of death among children under 5 years in Swaziland. Although it has been shown that early initiation of infants and children diagnosed with HIV on antiretroviral therapy (ART) significantly reduces mortality, many children do not initiate ART until at the later stages of disease. This study was designed to collect qualitative data from mothers and caregivers of HIV-positive children to identify the barriers to ART initiation. Focus group discussion (FGD) sessions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…We found that as people's health improved on ART, some individuals moved to places far from their ART refill clinics in pursuit of work to earn an income that resulted in missed ART refill appointments. The missed ART refill appointments could be due to either busy work schedules, or lack of transport fares, as described by other studies; 21,22 and strongly suggested that committed and well-supported biological caregivers are a key determinant to ART adherence as these experienced a stronger connotation to promote adherence. 23 Medication-related factors indicated that children who were instantly started on ART after diagnosis were twice more likely to adhere than those started later.…”
Section: Discussionmentioning
confidence: 80%
“…We found that as people's health improved on ART, some individuals moved to places far from their ART refill clinics in pursuit of work to earn an income that resulted in missed ART refill appointments. The missed ART refill appointments could be due to either busy work schedules, or lack of transport fares, as described by other studies; 21,22 and strongly suggested that committed and well-supported biological caregivers are a key determinant to ART adherence as these experienced a stronger connotation to promote adherence. 23 Medication-related factors indicated that children who were instantly started on ART after diagnosis were twice more likely to adhere than those started later.…”
Section: Discussionmentioning
confidence: 80%
“…This study uses a social ecological model (SEM) to explore how factors across multiple levels interact and influence ART adherence (Fig 1). The SEM is used in public health to understand the manner in which factors within multiple environmental domains exert an influence on individual health behaviors and outcomes [13,37,38].…”
Section: Methodsmentioning
confidence: 99%
“…A good proportion of women came only for delivery poorly followed (insufficient counseling, resistance to the screening test), in many small clinics in or out of the district with few information about the cascade PMTCT (Antenatal PMTCT and post-partum PMTCT). As Ahmed et al in a qualitative analysis, denial and guilt could be a reason of late initiation of ART among these pregnant women (Ahmed et al, 2017).…”
Section: Discussionmentioning
confidence: 83%